Analyzing Zuko’s Redemption Arc in Avatar: The Last Airbender Through Maslow’s Hierarchy of Needs - Sekarayu Sang Kinasih; Devi Hellystia (Journal of linguistics, culture and communication, 2025)
Character development in fiction often mirrors fundamental psychological struggles, making it a compelling area for analysis. Although previous studies have explored Avatar: The Last Airbender from literary and cultural viewpoints, there has been limited focus on Zuko’s redemption arc through the framework of Maslow’s Hierarchy of Needs. This study aims to analyze Zuko’s transformation from conflict to redemption, exploring not only Maslow’s stages of physiological needs, safety, love and belonging, esteem, and self-actualization but also the impact of sociocultural influences and family pressures on his development. Employing a descriptive qualitative approach, data were gathered from selected episodes of the series and analyzed through Maslow’s framework, supplemented by triangulation of theories to enhance the understanding of Zuko’s character. The findings indicate that Zuko’s journey through the hierarchy reflects both his internal conflicts and the evolving dynamics of his relationships, particularly with his father and Uncle Iroh, which play pivotal roles in his transformation. This study highlights how the fulfillment of human needs, alongside external sociocultural factors, shapes a character’s redemption arc, thereby fostering a deeper dialogue between psychology and narrative studies.